MUSICAL AND CREATIVE ENVIRONMENT AS A CONDITION FOR THE PROFESSIONAL ACTIVITY OF A TEACHER (European Journal of Interdisciplinary Research and Development, 2023)
In the study, an attempt was made to study the features of the musical and creative environment in the professional activities of a teacher. Goals and objectives of this work: consider the historical and theoretical aspects and prerequisites of the musical and creative environment (periods of formation of musical education); identify the key methodological systems of musical education and upbringing (components) as prior experience in music pedagogy; identify the features of the project method in the musical and creative environment, as a productive training for the future professional activity of a teacher.